PENGARUH KUALITAS PELAYANAN DAN INFORMASI TERHADAP KEPUASAN KONSUMEN (STUDI KASUS PADA PT BINTANG MOTOR) CABANG TANGERANG - Abdul Rohim, Muhammad; Mutmainnah (Journal of Research and Publication Innovation, 2024)
The purpose of this stu study was tο determine the effect of service quality and information quality on Consumer satisfaction at PT Bintang Motor branch Tangerang either partially or simultaneously. The method used is the associative method in taking the sample, the Slovin formula was used and obtained 98 respondents. The data analysis used validity test, reliability test, classical assumption test, regression analysis, determination coefficient analysis and hypothesis testing. The results of this study are Service quality and information have a significant effect ton consumer satisfaction with the regression equation Y= 9,641 + 0,411X1 + 0,354X2. The coefficient of determination is 52,4% ,while the remaining 47.6% is influenced by other factors. Hypothesis testing obtained the value of F count > F table or (52.373 > 2.700). Thus HO is rejected and H3 is accepted. This means that there is a significant effect simultaneously between service quality and information on consumer satisfaction at PT. Bintang Motor Branch Tangerang.